Characterization of a Red Beet Protein Homologous to the Essential 36-Kilodalton Subunit of the Yeast V-Type ATPase - Bauerle, Cynthia (American Society of Plant Physiologists, 1998)
V-type proton-translocating ATPases (V-ATPases) (EC 3.6.1.3) are electrogenic proton pumps involved in acidification of endomembrane compartments in all eukaryotic cells. V-ATPases from various species consist of 8 to 12 polypeptide subunits arranged into an integral membrane proton pore sector (V(0)) and a peripherally associated catalytic sector (V(1)). Several V-ATPase subunits are functionally and structurally conserved among all species examined. In yeast, a 36-kD peripheral subunit encoded by the yeast (Saccharomyces cerevisiae) VMA6 gene (Vma6p) is required for stable assembly of the V(0) sector as well as for V(1) attachment. Vma6p has been characterized as a nonintegrally associated V(0) subunit. A high degree of sequence similarity among Vma6p homologs from animal and fungal species suggests that this subunit has a conserved role in V-ATPase function. We have characterized a novel Vma6p homolog from red beet (Beta vulgaris) tonoplast membranes. A 44-kD polypeptide cofractionated with V-ATPase upon gel-filtration chromatography of detergent-solubilized tonoplast membranes and was specifically cross-reactive with anti-Vma6p polyclonal antibodies. The 44-kD polypeptide was dissociated from isolated tonoplast preparations by mild chaotropic agents and thus appeared to be nonintegrally associated with the membrane. The putative 44-kD homolog appears to be structurally similar to yeast Vma6p and occupies a similar position within the holoenzyme complex.